If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -12 = 3x + -6 Reorder the terms: -12 + 4x = 3x + -6 Reorder the terms: -12 + 4x = -6 + 3x Solving -12 + 4x = -6 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -12 + 4x + -3x = -6 + 3x + -3x Combine like terms: 4x + -3x = 1x -12 + 1x = -6 + 3x + -3x Combine like terms: 3x + -3x = 0 -12 + 1x = -6 + 0 -12 + 1x = -6 Add '12' to each side of the equation. -12 + 12 + 1x = -6 + 12 Combine like terms: -12 + 12 = 0 0 + 1x = -6 + 12 1x = -6 + 12 Combine like terms: -6 + 12 = 6 1x = 6 Divide each side by '1'. x = 6 Simplifying x = 6
| 4x-12=-3x-6 | | -3x+5=1x-5 | | y^4-13y^3=42y^2 | | 6=.5+2 | | 2m-3+m=15 | | 24n(n-1)=0 | | x^2-17x+84=0 | | 3x^2-x-6=0 | | -12x-4(5+10x)=11(-3x+12) | | 9x=5x+9x-15 | | c(c-17)=0 | | 3x+6=2x+9 | | 4=-0.8 | | 5x+5=5x+x+2 | | 10x+6=6x-8+10x-16 | | 12*11-20= | | 16x-9=5x+12x-20 | | 10x+9-11-x=-2(2x+4)-3(2x-2) | | 5*1+2*(3-1)=6 | | n-14n-6=-5 | | n-14n-6=-6 | | 4x+3=5x+4x-3 | | 5=2x+5x-2 | | 5*5-(25/5)=20 | | 5*5-(25/5)= | | 4=4x-2+2x | | 75=3(6x-5) | | 9x-9=3x+6+x+6 | | 5x+45+-89=90+41 | | a^3-16ab^2=0 | | 5x+45-89=90+41 | | 4(5-6)+6x=6 |